TRADISI TURUN MANDI DI KELURAHAN TANAH GARAM KOTA SOLOK (TINJAUAN SEMIOTIKA) - Syafri Multiara; Zona Rida Rahayu; Rini Wirasty B. (JELISA (Jurnal Edukasi dan Literasi Bahasa), 2022)
The tradition of going down the bath is not something that is done without the meaning behind it. A group of people carry out a custom or tradition without knowing the meaning of the custom itself which results in the community not understanding about the customs themselves. Therefore, it is feared that people's ignorance of these customs and especially the influence of foreign cultures into regional cultures, so that the cultural values contained in them will fade slowly. This research is qualitative research using descriptive methods. The findings of the semiotics review study are signs, emblems, and cues. Semiotic surveys are found in a series of events in the tradition of going down and down bathing in Tanah Garam Village of Solok City. In the data that has been obtained in the study, that the semiotics review of the series of events in the tradition of going down the bath in Tanah Garam Village of Solok City there are 59 data in total, signs (sign) there are 21 data, symbols (symbols) are contained 19 data, and the signal (signal/index) contained 19 data. The three components are interconnected signs, symbols, and signal in the study of semiotics cannot be separated from each other.